Effects of isosorbide dinitrate injection on acute myocardial infarction. A haemodynamic and gamma-angiographic study (author's transl) - Amor, M; Godenir, J P; Robinet, P; Karcher, G; Hocquard, C; Houppe, J P; Bertrand, A; Faivre, G (La Nouvelle presse medicale, 1982)
The haemodynamic and gamma-angiographic effects of isosorbide dinitrate (ISDN) injection were evaluated in 18 patients with recent myocardial infarction by measuring diastolic (DPAP) and systolic (SPAP) pulmonary artery pressures, diastolic (DAP) and systolic (SAP) systemic arterial pressures, cardiac index (CI) and heart rate (HR). Total ejection fraction (EF) was measured by radionuclide angiography. Within the first hour of treatment, there was a significant fall in DPAP (from 25.11 +/- 6.5 to 18.3 +/- 6 mmHg), SPAP (from 47 +/- 11.5 to 36.6 +/- 10 mmHg) and SAP (from 140 +/- 27.8 to 123 +/- 20 mmHg). Changes in DAP, CI and HR were not significant. The drug produced a significant increase in EF (from 32.6 +/- 15 to 35.3 +/- 15 p. cent). On the basis of these results the patients could be divided into three categories: -- Group I patients (n = 5) with EF greater than 45, in whom the haemodynamic effects (fall in DRAP from 20.8 +/- 4.2 to 16.3 +/- 3 mmHg) and the gamma-angiographic effects (increase in EF from 53.8 +/- 6 to 58.6 +/- 3 p. cent) were favourable. -- Group II patients (n = 5) with EF less than 40, in whom the haemodynamic effects (fall in DRAP from 29 +/- 8.5 to 17.8 +/- 6 mmHg) and the gamma-angiographic effects (increase in EF from 23 +/- 9 to 34 +/- 7 p. cent) were still favourable. -- Group III patients (n = 8) with low EF, in whom there were no significant changes in haemodynamic effects (DPAP from 25.3 +/- 3 to 23.4 +/- 5 mmHg) and gamma-angiographic effects (EF from 26 +/- 6 to 25 +/- 5 p. cent). This group corresponds to cases with very extensive necrosis of unfavourable outcome (4 deaths). One may therefore consider that the lack of effectiveness of ISDN in subjects with left ventricular failure and low EF is of poor prognosis and requires more aggressive therapy.